Human Interferon Alpha-2b: A Therapeutic Protein for Cancer Treatment - Ratih Asmana Ningrum (Scientifica)
Human interferon alpha (hIFNα) is a wide biological activity cytokine that is used in hepatitis and cancer treatments. It regulates many genes that are involved in antiviral and antiproliferative activities. This mini review focuses on human interferon alpha-2b (hIFNα-2b) as therapeutic protein for cancer treatment. The review covers hIFNα-2b molecular characteristic and its molecular mechanism by Janus activated kinase/signal transducer activation of transcription (JAK-STAT) pathway. The JAK-STAT pathway regulates not only proteins involved in inhibition of proliferation but also apoptosis. As additional discussion of clinical applications, the use of recombinant hIFNα-2b (rhIFNα-2b) as therapeutic protein in several types of cancer is also explained.